2018
DOI: 10.1002/jcp.27106
|View full text |Cite
|
Sign up to set email alerts
|

CTNNBIP1 downregulation is associated with tumor grade and viral infections in gastric adenocarcinoma

Abstract: Gastric cancer is a life-threatening disease; resulting from interaction among genetic, epigenetic, and environmental factors. Aberrant dysregulation and methylation changes in Wnt/β-catenin signaling downstream elements are a prevalent phenomenon encountered in gastric tumorigenesis. Also, viral infections play a role in gastric cancer development. CTNNBIP1 (β-catenin interacting protein 1) gene is an antagonist of Wnt signaling which binds to the β-catenin molecules. The CTNNBIP1 function as tumor suppressor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Previous researches showed that CTNNBIP1 negatively regulates cancer progression [ 17 , 31 ]. For example, CTNNBIP1 downregulation promotes progression of lung adenocarcinomas [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches showed that CTNNBIP1 negatively regulates cancer progression [ 17 , 31 ]. For example, CTNNBIP1 downregulation promotes progression of lung adenocarcinomas [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, increasing evidence has shown that the CTNNBIP1/β-catenin interaction can prevent the formation of the β-catenin/TCF/ LEF complex. As a result, it prevents the activation of the Wnt/β-catenin signaling pathway [95][96][97][98]. The upregulated circRNA_102171 facilitates the malignant behavior of papillary thyroid cancer by regulating the CTNNBIP1-mediated activation of the Wnt/β-catenin pathway.…”
Section: Wnt Pathway-related Circrnasmentioning
confidence: 99%
“…Epigenetics consist of DNA methylation, histone modification, histone acetylation, histone phosphorylation and also RNA remodeling which DNA methylation is the most important element [6][7][8][9][10][11][12]. Meanwhile, alongside with the investigation of epigenetics fluctuation in GI cancers, gene expression study must be added in order to have a better comparison and result [13][14][15][16][17][18][19][20].…”
Section: Epigenetic and Cancermentioning
confidence: 99%